2014
DOI: 10.1111/pin.12190
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of exon skipping and losartan on skeletal muscle of mdx mice

Abstract: Various attempts have been made to find treatments for Duchenne muscular dystrophy (DMD) patients. Exon skipping is one of the promising technologies for DMD treatment by restoring dystropin protein, which is one of the muscle components. It is well known that losartan, an angiotensin II type1 receptor blocker, promotes muscle regeneration and differentiation by lowering the level of transforming growth factor-beta1 signaling. In this study, we illustrated the combined effects of exon skipping and losartan on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Losartan treatment has been shown to increase the efficiency of myoblast cell therapy (Fakhfakh et al, 2012 ) and Adipose-Derived Stem Cell therapy (Lee et al, 2015 ). However, a study by Lee et al ( 2014 ) showed that although combined therapy with Losartan and exon skipping was beneficial in terms of muscle regeneration, the efficiency of exon skipping was lower in Losartan treated mice due to decreased in vivo morpholino penetration. In this study, Losartan was added prior to morpholino treatment, it would be interesting to see what happens when losartan treatment is started after the exon skipping treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Losartan treatment has been shown to increase the efficiency of myoblast cell therapy (Fakhfakh et al, 2012 ) and Adipose-Derived Stem Cell therapy (Lee et al, 2015 ). However, a study by Lee et al ( 2014 ) showed that although combined therapy with Losartan and exon skipping was beneficial in terms of muscle regeneration, the efficiency of exon skipping was lower in Losartan treated mice due to decreased in vivo morpholino penetration. In this study, Losartan was added prior to morpholino treatment, it would be interesting to see what happens when losartan treatment is started after the exon skipping treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Duchenne muscular dystrophy (DMD) is an Xlinked inherited muscular disorder characterized by the absence of dystrophin [1]. Without dystrophin, the muscles undergo repetitive degeneration and regeneration cycles leading to muscle fibrosis and weakness [2]. Various attempts have been made to overcome DMD, including steroid treatment [3,4], gene therapy [5,6] and stem cell therapy [7].…”
Section: Introductionmentioning
confidence: 99%